The Correlation of Body Mass Index with Visceral and Subcutaneous Adipose Tissue Volume in Patients that Performed Abdominal CT scan at RSUP H. Adam Malik Medan - Duma Ratna Sari Nasution; Netty Delvrita Lubis; Naomi Niari Dalimunthe (Buletin Farmatera, 2023)
Visceral and subcutaneous adipose tissue (VAT and SAT), and excess body mass index (BMI) act as cardiometabolic risk factors. BMI only describes the ratio of body weight to height in general. Abdominal CT scan is the gold standard in the examination of VAT and SAT volumes. The purpose of this study is to analyze the correlation between BMI with VAT and SAT in patients that performed CT scans of the abdomen. A total of 60 patients who underwent CT scans of the abdominal region at the Radiology Department of the RSUP H. Adam Malik Medan from July to August 2022 participated in this cross-sectional study. The BMI was calculated from measurement and volume of VAT and SAT were obtained from CT scans of the abdominal region at the fourth lumbal level, using 3D smart segmentation. Among of samples was 51.7% male. Average of age and BMI are 49.3 12.18 years and 25.58 kg/m2. Average of VAT and SAT volume value are 678.13 436.09 cm3 and 1708.76 1068.99 cm3. There is a moderate positive correlation between BMI and VAT (r=0.687) and BMI and SAT (r=0.669) with p0.001.